2019
DOI: 10.22159/ajpcr.2019.v12i18.34175
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ulcer Agents: A Pharmacological Update of the Past Ten Years

Abstract: New anti-ulcer substances are still vitally necessary for the people of countries such as India and South Africa to avoid high cost of the most prescribed marketed anti-ulcer drugs (proton-pump inhibitors). New candidate against gastric ulcer is also necessary to avoid the potential problem (enterochromaffin-like cell hyperplasia may be induced) associated with the long-term use of synthetic proton-pump inhibitors. However, the search for the novel entity against ulceration is challenging because of the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Te monoterpenes menthol (35-45%) and menthone (15-20%) are the major constituents in the essential oil of Mentha x piperita L., and menthofuran (2-7%) is one of the other present components [16,17]. Menthol had its antispasmodic [18,19] and gastroprotective [20] activities previously investigated, whereas isomenthone showed protective activity against tumor necrosis factor-α-induced cell death [21]. Interestingly, a previous study has reported the menthofuran-induced gastroprotective efect by underlying antioxidant mechanisms [22].…”
Section: Introductionmentioning
confidence: 99%
“…Te monoterpenes menthol (35-45%) and menthone (15-20%) are the major constituents in the essential oil of Mentha x piperita L., and menthofuran (2-7%) is one of the other present components [16,17]. Menthol had its antispasmodic [18,19] and gastroprotective [20] activities previously investigated, whereas isomenthone showed protective activity against tumor necrosis factor-α-induced cell death [21]. Interestingly, a previous study has reported the menthofuran-induced gastroprotective efect by underlying antioxidant mechanisms [22].…”
Section: Introductionmentioning
confidence: 99%